Geochemical features of the pseudotachylytes in the Longmen Shan thrust belt, eastern Tibet. (30th April 2019) - Wang, Huan; Li, Haibing; Si, Jialiang; Zhang, Lei; Sun, Zhiming
Abstract: Pseudotachylytes, produced by frictional heating during seismic slip, convey information that is critical to understanding the physics of earthquakes, their geochemical features triggered by frictional melting shed light on the seismic processes and frictional strength as well. However, whether their geochemical properties changed during exhumed process is still uncertain. To provide insight to this topic, we conducted a case study of pseudotachylytes in the Longmen Shan thrust belt, eastern Tibet. Pseudotachylyte samples drilled from the WFSD boreholes at deep depth and collected at surface outcrops were analyzed by μXRF core scanner to estimate their geochemical variations. Macro- and micro-structural observations suggest that the pseudotachylytes are from melt-origin. Comparative analyses of the geochemical characteristics between surface and deep pseudotachylytes show that the former are K- and Ti-depleted in an oxidation environment, while the latter have low Si, high K, Fe, Ti and Mn in a reductive environment. Besides the selective melting process, another reasonable explanation for these differences is that the geochemical properties of the surface pseudotachylytes have changed due to the prolonged fluid influence during the long-term exhumation processes, which cannot exactly reflect the nature of the initial frictional melt. Therefore, we conclude that primary pseudotachylytes are characterized by enrichment of K, Fe, Ti, Mn and depletion of Si. The frictional melt was generated in high-temperature reductive environment, and fluids have influenced their chemical composition during the exhumation process. These results are of great significance for correctly understanding earthquake mechanics and fault behavior.